Synthesis, structure determination, and biological evaluation of phenylsulfonyl hydrazide derivatives as potential anti-inflammatory agents. Issue 21 (1st November 2016) - Park, Eun Beul; Kim, Kwang Jong; Jeong, Hui Rak; Lee, Jae Kyun; Kim, Hyoung Ja; Lee, Hwi Ho; Lim, Ji Woong; Shin, Ji-Sun; Koeberle, Andreas; Werz, Oliver; Lee, Kyung-Tae; Lee, Jae Yeol
Graphical abstract: Abstract: In our previous research, a novel series of phenylsulfonyl hydrazide derivatives were found to reduce LPS-induced PGE2 levels in RAW 264.7 macrophage cells via an inhibition of mPGES-1 enzyme. Recently, it was found that a regioisomeric mixture of phenylsulfonyl hydrazide was formed depending on the reaction conditions, which favor either of two regioisomers. One regioisomer corresponds to a kinetic product (7a –7c ) and the other regioisomer corresponds to a thermodynamic product (8a –8c ). Among them, the structure of kinetic product7b was confirmed by measuring single X-ray crystallography. In vitro PGE2 assay studies showed that the kinetic product (7a and7b ; IC50 = 0.69 and 0.55 μM against PGE2 ) is generally more potent than the thermodynamic product (8a and8b ; IC50 = >10 and 0.79 μM against PGE2 ). A molecular docking study also exhibited that the kinetic product (7a ) has a higher MolDock Score (−147.4) than that of8a (−142.4), which is consistent with the PGE2 assay results. A new potent phenylsulfonyl hydrazide (7d ; IC50 = 0.06 μM against PGE2 ) without affecting COX-1 and COX-2 enzyme activities was identified based on these overall results.